Utility and safety of plasma exchange in paediatric neuroimmune disorders. (18th January 2019) - Eyre, Michael; Hacohen, Yael; Lamb, Kate; Absoud, Michael; Agrawal, Shakti; Gadian, Jonathan; Gupta, Rajat; Kneen, Rachel; Milford, David V; Philip, Sunny; Rose, Katie; Smith, Martin; et al.
Abstract : Aim: Our aim was to ascertain the indications, side effects, and outcomes in children receiving therapeutic plasma exchange (TPE) for neurological disorders. Method: Medical records were retrospectively reviewed for 58 consecutive children (age ≤16y) undergoing 67 courses of TPE across four tertiary centres. Patient characteristics, treatment schedules, complications, and outcomes were analysed. Results: Median age at initiation of TPE was 9 years (range 1–15y). Indications included peripheral nervous system (PNS; n =18) and central nervous system (CNS; n =40) disorders. Courses comprised a median six exchanges (range 2–179) over 8 days (range 3–466). Forty‐two out of 58 (73%) children were severely disabled (bedridden) at initiation and 24 out of 58 (41%) were admitted to intensive care units. Treating clinicians' impression of response was positive in 16 out of 18 of those with PNS disorders versus 22 out of 40 with CNS disorders ( p =0.016). Improvements in disability (modified Rankin Scale) occurred in 13 out of 58 (22%) children by completion of TPE ( p =0.003). Complications occurred in 40 out of 67 (60%) courses, of which 16 out of 67 (24%) were line related. Potentially life‐threatening complications occurred in 2 out of 67 (3%) courses. Interpretation: This cohort study provides safety and efficacy information for clinicians and families and a basis for future prospective studies. What this paper adds: Disability scores for severe neuroimmune disorders remained stable or improved during therapeutic plasma exchange treatment. Complications occurred frequently but were typically mild and correctable. What this paper adds: Disability scores for severe neuroimmune disorders remained stable or improved during therapeutic plasma exchange treatment. Complications occurred frequently but were typically mild and correctable. This article is commented on by Nosadini and Dale on pages 504–505 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Utilidad y seguridad del intercambio de plasma en trastornos neuroinmunes pediátricos : Objetivo: Nuestro objetivo fue determinar las indicaciones, los efectos secundarios y los resultados en niños que recibieron intercambio terapéutico de plasma (TPE) para trastornos neurológicos. Método: Se revisaron retrospectivamente los registros médicos de 58 niños consecutivos (≤16 años) que se sometieron a 67 cursos de TPE en cuatro centros terciarios. Se analizaron las características de los pacientes, los esquemas de tratamiento, las complicaciones y los resultados. Resultados: La edad mediana al inicio de la TPE fue de 9 años (rango 1‐15 años). Las indicaciones incluían trastornos del sistema nervioso periférico (SNP; n = 18) y del sistema nervioso central (SNC; n = 40). Los cursos comprendieron una mediana de 6 intercambios (rango 2–179) durante 8 días (rango 3–466). Cuarenta y dos de 58 (73%) niños presentaban un grado de discapacidad severa (postrados en cama) al inicio y 24 de 58 (41%) fueron ingresados en unidades de cuidados intensivos. El tratamiento de la impresión de respuesta de los médicos fue positivo en 16 de 18 de las personas con trastornos de SNP versus 22 de 40 en trastornos del SNC ( p = 0, 016). Las mejoras en la discapacidad (escala de Rankin modificada) se produjeron en 13 de los 58 (22%) niños al completar el TPE ( p = 0, 003). Las complicaciones ocurrieron en 40 de 67 cursos (60%), de los cuales 16 de 67 (24%) estaban relacionados con la línea. Complicaciones potencialmente peligrosas para la vida ocurrieron en 2 de 67 (3%) cursos. Interpretación: Este estudio de cohorte proporciona información de seguridad y eficacia para profesionales y familiares y una base para futuros estudios prospectivos. Resumo: Utilidade e segurança da transferência de plasma em transtornos neuroimunes pediátricos : Objetivo: Nosso objetivo foi verificar as indicações, efeitos colaterais, e resultados em crianças recebendo transferência terapêutica de plasma (TTP) para transtornos neurológicos. Método: Registros médicos foram retrospectivamente revisados para 58 crianças (idade ≤16a) passando por 67 cursos de TTP em quatro centros terciários. Características dos pacientes, rotina de tratamento, complicações e resultados foram analisados. Resultados: A idade mediana ao início da TTP foi 9 anos (variação 1‐15 anos). Indicações incluíram transtornos do sistema nervoso periférico (SNP; n = 18) e sistema nervoso central (SNC; n = 40) disorders. Os cursos compreenderam uma mediana de seis transferências (variação 2–179) em 8 dias (variação 3–466). Quarenta e duas em 58 (73%) crianças estavam severamente incapacidadas (acamadas) no início e 24 em 58 (41%) foram admitidas em unidades de cuidado intensivo. A impressão de resposta dos clínicos que as tratavam foi positiva em 16 de 18 daquelas com transtornos do SNP versus 22 de 40 daquelas com desordens do SNC ( p = 0, 016). Melhoras na incapacidade (Escala de Rankin modificada) ocorreram em 13 de 58 (22%) crianças ao final da TTP ( p = 0, 003). Complicações ocorreram em 40 de 67 (60%) cursos, dos quais 16 em 67 (24%) eram relacionados à linha. Complicações com potencial risco de vida ocorreram em 2 de 67 (3%) cursos. Interpretação: Este estudo de coorte fornece informação sobre a segurança e eficácia para clínicos e famílias, e uma base para futuros estudos prospectivos.